The moderating role of emotional intelligence in the relationship between perceived academic control and English achievement among Chinese ethnic minority college students: A theoretical perspective - Mingxing Li; Asmaa AlSaqqaf; Sabariah Sharif (Academia Industry Networks, 2025)
This research explores how emotional intelligence moderates the perceived academic control /English achievement relationship among ethnic minority undergraduates in Yunnan, China. These students face additional challenges in multilingual educational contexts, culturally and linguistically. This research explores how PAC affects their English proficiency. Furthermore, it investigates how EI moderates the strength of this relationship. A quantitative methodology and instruments of the Self-Report Emotional Intelligence Scale and the Perceived Academic Control Scale will be used with simple random sampling. This study seeks to provide insights into the interactions of PAC, EI, and English achievement, ultimately providing strategies to facilitate academic success in this unique context. The results are expected to underscore the importance of EI in supporting students' English learning outcomes, especially in the context of multilingualism and cultural diversity.